Pengaruh Budaya Organisasi dan Stres terhadap Komitmen Organisasi dan Kepuasan Kerja (Studi di Kepolisian Negara RI Sektor, Kepolisian Negara RI Daerah Jawa Timur) - S., Chairul Muriman; Idrus, M. S.; Thoyib, Armanu; S., Margono (Jurnal Aplikasi Manajemen, 2008)
This research aimed to: (1) analyze the effect of organizational culture on organization commitment at District Police Office, East Java Police Department (2) analyze the effect of organizational culture on job satisfaction at District Police Office, East Java Police Department. (3) analyze the effect of stress on organization commitment at District Police Office, East Java Police Department, (4) analyze the effect of stress on job satisfaction at District Police Office, East Java Police Department, (5) analyze the effect of organization commitment on job satisfaction at District Police Office, East Java Police Department, and (6) analyze the effect of job satisfaction on organization commitment at District Police Office, East Java Police Department. The research design was conducied by using causality analysis with quantitative approach and also survey methodology. The population in this study is all person District Police Office in East Java. The total of population are 44.557 person. Samples has been taken by using multistage cluster sampling Some respondents are consisted of the head and deputy of district police office and also other functions are 412 respondent. Using Structural Equation Modeling (SEM) with the AMOS 6.0 software, the results of hypothesis analysis shows that: (1) organizational culture has positive effect on organization commitment significantly (H, accepted). (2) organizational culture has positive effect on job satisfaction significantly (H, accepted), (3) stress has negative effect on organization commitment significantly (H, accepted), 4) stress has negative effect on job satisfaction significantly (H, accepled). (5) organization commitment has positive effect on job satisfaction significantly (H, accepted), and (6) job satisfaction has positive effect on organization commitmeni significantly (H, accepted).